Progress in Interdisciplinary Research: Evidence From the COVID-19 Pandemic - Huang, Shufang (SAGE open, 2025)
Although the COVID-19 pandemic has largely subsided, it remains crucial to reflect on past experiences and shortcomings to better prepare for potential future outbreaks. Effective outbreak management is a complex scientific challenge that demands robust interdisciplinary collaboration. However, there is currently a lack of quantitative and objective assessments of progress in interdisciplinary research on coronaviruses, particularly measures that directly evaluate the extent of such collaborations. In this study, we employed Python-based algorithms to analyze 156,674 publications from the Web of Science database, tracing the development of coronavirus research and interdisciplinary collaboration. Our findings reveal a significant upward trend in both the volume of coronavirus research and the intensity of interdisciplinary collaboration over the past 5 decades. Notably, major outbreaks have acted as critical catalysts, driving substantial advancements in this field. The past 2 decades, marked by three major coronavirus outbreaks, have seen dramatic growth in the scale and depth of interdisciplinary studies. Nevertheless, achieving seamless cross-disciplinary integration remains a persistent challenge. This study offers valuable insights for fostering interdisciplinary collaboration and optimizing academic discipline structures in universities.